Phytochemical Analysis, Antioxidant and Cytotoxic Activity of Lannea egregia Engl. & K. Krause Stem Bark Extracts - Akoro, Seide M; Omotayo, Mutiat A; Ogundare, Oyinlade C; Akpovwovwo, Stemon A; Bello, Gbemileke P (UI Scholars Hub, 2022)
This study investigates the phytochemical contents, antioxidants and cytotoxic activities of Lannea egregia Engl. & K. Krause stem bark extracts. Secondary metabolites were extracted using n-hexane, ethyl acetate, and ethanol by successive maceration. The concentrated extracts were subjected to preliminary phytochemical screening using standard procedures. The crude flavonoid was obtained from the plant material using Harborne’s method and then profiled using high-performance liquid chromatography (HPLC). The antioxidant activities of the plant extract were assessed using reducing power assay and DPPH scavenging activity, while the cytotoxic activity was determined using the brine shrimp lethality assay. The crude extract of n-hexane or LEHe (0.86%), ethyl acetate or LEEa (1.42%), ethanol or LEEt (3.32%), and flavonoid or LEF (9.7+-0.01%) were obtained from the plant material, with flavonoids, anthraquinone, terpenoids, and tannins detected. The ethyl acetate extract and the crude flavonoid have the highest and comparable DPPH radical scavenging activity at IC50 of 22.98 ± 0.07 μg/mL and 22.48 ± 1.02 μg/mL respectively, the greatest reducing property being exhibited by the ethanol extract. The most cytotoxic activity was observed in the n-hexane extract at LC50 of 8.70 ± 0.58 μg/mL. HPLC detected catechin, p-coumaric acid, ferulic acid, rutin, apigenin, kaempferol and quercetin. In conclusion, Lannea egregia stem bark extracts possess antioxidant and cytotoxic activities and could be explored for new drugs in the management of cancer.